Butinage; The Art of Religious Mobility - Gez, Yonatan N.; Droz, Yvan; Rey, Jeanne; Soares, Edio (University of Toronto Press, 2024)
Using the metaphor of “religious butinage,” this book explores the idea of religious practices as predominantly mobile, eschewing rigid frameworks oriented around exclusive categories of membership and conversion.